2022
DOI: 10.1002/humu.24347
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing demonstrates high diagnostic yield in children with undiagnosed global developmental delay/intellectual disability: A prospective study

Abstract: Genome sequencing (GS) has been used in the diagnosis of global developmental delay (GDD)/intellectual disability (ID). However, the performance of GS in patients with inconclusive results from chromosomal microarray analysis (CMA) and exome sequencing (ES) is unknown. We recruited 100 pediatric GDD/ID patients from multiple sites in China from February 2018 to August 2020 for GS. Patients have received at least one genomic diagnostic test before enrollment. Reanalysis of their CMA/ES data was performed. The y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…ES is unable to cover all the exomes and is prone to having false negative gaps in GC-rich regions, repetitive regions, regions with pseudogenes, and regions with high homology [ 80 ]. Additionally, low probe affinity for the highly variable regions and missed coverage could both lead to false negative results [ 7 ]. The regions with reduced coverage depend on sequencing metrics and may differ between labs.…”
Section: Genetic Diagnostic Tools For Unexplained Intellectual Disabi...mentioning
confidence: 99%
See 2 more Smart Citations
“…ES is unable to cover all the exomes and is prone to having false negative gaps in GC-rich regions, repetitive regions, regions with pseudogenes, and regions with high homology [ 80 ]. Additionally, low probe affinity for the highly variable regions and missed coverage could both lead to false negative results [ 7 ]. The regions with reduced coverage depend on sequencing metrics and may differ between labs.…”
Section: Genetic Diagnostic Tools For Unexplained Intellectual Disabi...mentioning
confidence: 99%
“…GS has the potential to become the first-tier etiologic evaluation of GDD/ID, especially in identifying short segment variants missed by CMA, and CNV and non-coding segment deletions or allele dropouts missed by ES [ 7 ]. The challenge in GS is the variant prioritization and interpretation of these complex, rare, and non-coding region variants.…”
Section: Genetic Diagnostic Tools For Unexplained Intellectual Disabi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequencing (GS) is an NGS approach that determines the sequence of most of the DNA of the entire genome of an individual. The main advantage of GS over ES is the ability to query intronic regions, and its superior ability compared with ES to detect structural rearrangements including small and large CNVs [ 43 , 65 ]. GS is not yet clinically available in most centers, and its use is still mainly restricted to research paradigms.…”
Section: Genetic and Metabolic Investigations In Children With Gdd/idmentioning
confidence: 99%
“…GS is not yet clinically available in most centers, and its use is still mainly restricted to research paradigms. One study demonstrated that the addition of GS to the investigation of patients with GDD/ID following unrevealing initial testing (either CMA, ES or both) had a diagnostic yield of 21% [ 65 ]. The yield was 64% if only a CMA had been previously performed and 14% if ES was performed [ 65 ].…”
Section: Genetic and Metabolic Investigations In Children With Gdd/idmentioning
confidence: 99%